The Role of the Mosque in Strengthening the Neighborhood Relationship. Applied Study on Mosques of Buraidah City - AL-Harbi, Yasser Saleh (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the role of the mosque in strengthening the neighborhood relationship. The researcher used the social survey method; To achieve the objectives of the study, and answer its questions through the use of the questionnaire tool. Research community and sample: imams of mosques and mosques in the city of Buraidah; A random sample of (304) imams; The results of the study showed that the vast majority of the imams of mosques in the city of Buraidah have a high level of education; The percentage of those holding a university degree and above was (87.5%). The majority of imams are young men; The percentage of those under 40 years old reached (80%) of the study sample. Our mosques also lack social activities; The absence of facilities and buildings belonging to the mosque to help in the establishment of such activities. In light of the results, the researcher recommended reconsidering the design of mosques in the future; To become attractive places for the residents of the neighborhood by placing halls and facilities belonging to the mosque instead of the courtyard, which is not usually used; So that social, educational and training activities are held in these halls, and the people of the neighborhood benefit from them. Their relationship increases through their meeting with each other periodically, and the creation of an encouraging reward for each distinguished imam; To motivate him and others to do their best to serve the people of the neighborhood.
Keywords: mosque; neighborhood; relationship; promotion; activity; imams